Ventricular Arrhythmia Risk Stratification Among Patients With Cardiac Resynchronization Therapy Devices - Ueda, Nobuhiko; Ishibashi, Kohei; Noda, Takashi; Oka, Satoshi; Miyazaki, Yuichiro; Wakamiya, Akinori; Nakajima, Kenzaburo; Kamakura, Tsukasa; Wada, Mitsuru; Inoue, Yuko; Miyamoto, Koji; Nagase, Satoshi; et al. (Circulation Reports, 2025)
Background: Patients with left ventricular (LV) dysfunction have a higher risk of ventricular arrhythmia (VA) compared with those without, and are candidates for implantable cardioverter defibrillator (ICD). Response to cardiac resynchronization therapy (CRT) decreases the risk of VA; however, selection of a suitable CRT device remains challenging.Methods and Results: In 678 patients with a CRT/ICD device and LV dysfunction, we investigated 325 CRT and 142 ICD patients for primary prevention. VA was defined as lasting ≥30 s or being treated with an ICD. CRT non-responders were defined as patients without reduced LV end-systolic volume ≥15%. During the follow-up period, 98 (21%) patients had a VA event (CRT 71 [22%] vs. ICD 27 [19%]; P=0.49). The VA risk score was calculated by summing values for non-left bundle branch block, left atrial diameter >45 mm, persistent atrial fibrillation, male sex, LV ejection fraction <25%, and ischemic cardiomyopathy. Our results showed that the VA risk score stratified the risk of VA among CRT patients (P<0.01), but was not significant for ICD patients (P=0.24). Patients with a VA risk score ≥4 (divided by receiver operating characteristic analysis) had a higher risk of VA among CRT patients (log rank P<0.01); however, it was not significant for ICD patients (log rank P=0.71).Conclusions: The VA risk score could be a useful indicator for VA among CRT candidates.